SUBJECTIVE WELL-BEING PADA MAHASISWA PERANTAUAN ASAL LUAR JAWA YANG KULIAH DI UNNES DITINJAU DARI JENIS KELAMIN - Purnama, Mahadika Yuda (SOUL : Jurnal Pemikiran dan Penelitian Psikologi, 2024)
This research aims to determine the description and comparison of the level of quality of subjective well-being among overseas students from outside Java who study at Semarang State University (UNNES) based on gender. The criteria for respondents in this research were overseas students from Semarang State University (UNNES). This research uses a quantitative approach with a descriptive comparative design. The sampling technique used in this research is simple random sampling. The number of samples in this study was 100 individuals. The data analysis techniques used in this research are descriptive analysis and t test using statistical software. Sig value. (two-tailed) in the T Test, a value of (0.369 > 0.05) was obtained. These results show that the quality level of subjective well-being in male overseas students from outside Java who study at Semarang State University (UNNES) is slightly better when compared to the level of subjective well-being quality in female overseas students, although there is no significant difference. significant between the two.